Caregiving for a Companion Animal Compared to a Family Member: Burden and Positive Experiences in Caregivers - Britton, Karysa; Galioto, Rachel; Tremont, Geoffrey; Chapman, Kimberly; Hogue, Olivia; Carlson, Mark D.; Spitznagel, Mary Beth (Frontiers in Veterinary Science, 2018)
Introduction: Research in human caregiving shows burden is often present in the caregiver, and can be reduced by interventions that increase positive perceptions of caregiving. Recent work suggests burden is also present in owners of a seriously ill companion animal. To help determine if findings from the human caregiving literature are likely to generalize to companion animal caregiving, we undertook a comparison of burden and positive aspects of caregiving in these groups. Material and Methods: Caregivers recruited through social media disease support and information groups completed self-report questionnaires of burden and positive aspects of caregiving in an online research protocol. Owners of a seriously ill companion animal (n=117) and caregivers of a family member with dementia (n=252) were cross-sectionally compared. Analyses in the full sample were repeated in a subset (n=75 per group) of caregivers with blindly matched demographic profiles. Results: Burden was elevated in both dementia and companion animal caregiver groups, though higher overall for dementia caregivers (p<.001 for full and matched samples). In contrast, greater positive aspects of caregiving were reported by companion animal caregivers (p<.001 for full and matched samples). In both groups, positive aspects of caregiving were negatively associated with burden (full sample p<.001; matched sample p<.05). Exploratory item analyses suggested the two groups show comparable experiences of fearing the future, guilt, and financial strain (p=ns for full and matched sample). Discussion: Although both groups showed elevated burden, companion animal caregivers reported less burden and a more positive appraisal of caregiving. Elements of burden showing similarities across groups provide a foundation for understanding caregiver burden in the companion animal owner. The inverse correlation between positive aspects of caregiving and burden suggests the impact of positive caregiving experiences should be considered in burden interventions, but because companion animal owners already positively appraise caregiving, enhancing positive aspects of caregiving may not offset burden as it does in human caregiving samples.